Development of Local Chicken Production Based on Local Feed Ingredients - Hidayat, Cecep (Indonesian Animal Sciences Society, 2012)
Development of local chicken production based on local feed ingredient is in line with the vision of Indonesian goverment to fulfill meat and egg national requirement based on local resources. There are two big problem which become stumblingblock in developing local chicken production. The first problem is the difficulty to get day old chick of local chicken. This problem can be solved by integrating breeder institutions belong to goverment with research institution and with local chicken producer association. The second problem is the low performance of local chicken. To improve local chicken performance, it can be done by improving the breed, feed and management. Several research results show that good performance of local chicken were obtained by inclusion of local feed ingredients in the ration. Therefore, development of local chicken production based an local feed resources can be applied. Key words: Development, local chicken, local resources